Development of a radio mode for the long wavelength array (LWA) receiving system to study the equatorial aeronomy - Estalla, B. (2025)
Instituto Geofísico del Perú (IGP), through its scientific facility at the Jicamarca Radio Observatory (JRO), monitors the upper atmosphere with different instruments: radars, GNSS receivers, magnetometers, among others. Through a National Science Foundation (NSF) MRI award, two Long Wavelength Array (LWA) receiving stations will be installed at 50 km south (Santa María) and 170 km east (Huancayo) of Jicamarca. Each station is composed of 256 dual-polarization antennas circularly distributed with a diameter of 100 m. In this poster, we present the development of the radio receiver mode for the Long Wavelength Array (LWA). The receiver consists of 16 AMD Zynq UltraScale+ MPSoC ZCU102 devices and 128 ADS5296A ADCs, configured for 12-bit resolution with a sampling rate of 160 MSPS.